Study on Factors Related to Eating Habits and Nutritional Status of The Elderly at The Rural and Urban Area - Lina Herlina; Emma S Wirakusumah; Lilik Noor Yuliati (Media Gizi dan Keluarga, 2001)
The study show result that the average educational level, the average expenses of consumption, the average level of the eating habits, the average body mass index in both area are clearly different. The average level of nutrition knowledge and health of the elderly in the rural areas proved differently with those in the urban. The average of teeth amount of the elderly in the rural is not clearly different with those in the urban. Almost all the average level of consumption of the nutrient elements (Energi, Protein, Vit.A, Vit.C, Ca, Fe) in both area, none of them reach 100,00 % of the Recommended Dietary Allowances, except for the level of consumption of Phosphor and Vit.B1 (urban). of the elderly people in both area categorized into good nutrition status, and both clearly different. The eating habits do not affect the nutrition status of the elderly people. The factors that affects towards the eating habit of the elderly people are knowledge and health.